Effect of Amino Acid Substitutions Within the V3 Region of HIV-1 CRF01-AE on Interaction with CCR5-Coreceptor - Sayamon Hongjaisee (2018)
© Copyright 2017, Mary Ann Liebert, Inc. 2017. Specific amino acids within the V3 loop of HIV-1 CRF01-AE envelope glycoprotein that are involved in the interaction with CCR5/CXCR4 coreceptors, are not well characterized. We generated V3 mutants using polymerase chain reaction (PCR)-based site-directed mutagenesis of HIV-1 CRF01-AE R5-env plasmids at specific positions. Mutant viruses were produced by env-pseudotyped virus assay, tested for coreceptor usage using U373.R5 and U373.X4 cells, and viral entry was assessed with luciferase activity measurement. All viruses, harboring either single or double mutations, used the CCR5 coreceptor. However, those containing a single substitution at positions 7, 11, 18, and 32 and those with mutations at positions 5/32 and 18/32 had reduced infectivity. Only virus with arginine substitution at position 11 seemed to be involved in CXCR4 coreceptor usage. Our results suggest that some V3 positions may be necessary for the binding to coreceptor, but not for the switch of coreceptor usage.